Penggunaan Metode SAW dalam Pemilihan Pegawai Terbaik Berdasarkan Kriteria Kinerja - Sihombing, Johanes Mula Febrian; Sadewo, Riski Probo; Ramadhani, Faiz Dzaki; Achmad, Ivan Faturrochman; Anshor, Abdul Halim (Jurnal Ilmiah SINUS, 2025)
To determine the best employees based on various performance criteria, such as work quality, punctuality, discipline and initiative, this research examines the Simple Additive Weighting (SAW) method. This method was chosen because of its ability to report employee evaluations and weightings objectively through normalization and assigning weights according to the level of importance of each criterion. This method collects employee performance data from trusted literature sources such as Google Scholar and SINTA, and uses calculations and rankings to produce a list of employees with the highest scores that can be used for promotions or awards. The research results show that the SAW method can be relied on in the performance-based decision making process and helps companies manage human resources better, increase employee motivation, and create a more productive work environment. For future research, this method could be further developed by adding standards such as adaptability and leadership, and testing it on various industries to see if it is suitable for them.